Efectos del herbicida nicosulfuron sobre malezas y genotipos de maíz (Zea mays L.) en el valle del Río Carrizal - Intriago Douglas, Junior José (2024)
The objective of this research was to evaluate the effect of the herbicide nicosulfuron on weeds and different genotypes of corn in the Carrizal River valley. The study was carried out at the “Manuel Félix López” Higher Polytechnic Agricultural School of Manabí, using a randomized block design (RCD) with an AxB+1 factorial arrangement. Ten treatments were applied in three replicates, with an experimental unit composed of ten pots per treatment. The study analyzed the effects of the herbicide nicosulfuron on corn seedlings throughout different phenological stages, evaluating the variation of toxicity with the dose of the herbicide and the phenological state of the plant, as well as the interactions between these factors. The results showed that higher doses of nicosulfuron caused greater toxicity in the three corn genotypes evaluated. The Salprieta genotype turned out to be the most sensitive compared to the improved genotypes INIAP 543 and INIAP H-601. Toxicity was particularly high in phenological stages V2 and V3, suggesting that nicosulfuron applications should preferably be made in stage V1 and, at most, in V2. Regarding weed control, higher doses of nicosulfuron showed greater effectiveness in controlling the species Echinochloa spp., Eleusine indica and Amaranthus retroflexus, according to the ALAM scale (1974). However, despite the continuous application of the herbicide, it was detected that the Eleusine indica shows signs of resistance to nicosulfuron. Although the level of control achieved is close to optimal standards, additional dose adjustments or implementation of complementary control strategies may be necessary to improve weed management and achieve complete suppression.